Prognostic factors in mandibular gingival squamous cell carcinoma: A 10-year retrospective study. Issue 2 (February 2017) - Niu, L.X.; Feng, Z.E.; Wang, D.C.; Zhang, J.Y.; Sun, Z.P.; Guo, C.B.
Abstract: The mandibular gingiva is the second most common site of oral cavity squamous cell carcinoma. This retrospective study was designed to determine the clinicopathological features of squamous cell carcinoma of the mandibular gingiva (MGSCC) and to establish a new risk model to predict overall survival. The study included 207 patients with primary MGSCC from January 2000 to September 2009. The medical charts were reviewed and data related to clinical characteristics, treatment provided, histopathological analysis, and follow-up were recorded. All patients underwent surgery as the first-line therapy; follow-up ranged from 1 to 171 months (median 63 months). Clinical characteristics and pathological outcomes were analyzed with respect to the 5-year overall survival rate. A survival risk model was established, and patients were classified into low-, moderate-, and high-risk groups based on the prognostic index designed in this study. The 5-year overall survival rates for the low-, moderate-, and high-risk groups were 92.3%, 76.9%, and 34.2%, respectively. Pathological node metastasis, perineural invasion, and extracapsular spread were the most significant predictive factors for 5-year overall survival. MGSCC is not aggressive, and the survival outcomes of MGSCC are better than those of squamous cell carcinoma (SCC) at other sites. It is suggested that patients with T2–T4 tumours undergo elective neck dissection and those with T1 tumours be followed up without addressing the neck.